Cult Film dan Analisa Semiotika Film Pada Nagabonar Jadi 2 - Akhmad Riza Faizal (Jurnal ILMU KOMUNIKASI, 2009)
Abstract: Cult films phenomena have attracts lots of discussion among film critics or communication experts especially for those who studied media, nevertheless research on the films using semiotic remains sparsely. This essay mainly discusses about intertextuality within Nagabonar Jadi 2 based on Umberto Eco’s conception about cult film and attempts to bear its narrative meaning using Greimas’ Rectangle, one among other semiotic methods. The research founded that the film has four propositions of narrative within the film which are nationalism, anti-nationalism, non nationalism, and non anti-nationalism. Salutes and flapping the national flag are the synecdoche of nationalism in this film.